Penerapan Metode Pembelajaran Konvensional dan Reading Guide Untuk Meningkatkan Prestasi Belajar Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam Kelas XI IIS di MA Unggulan An Nuur Pare Kediri - Muhammad Asrori; Haryadi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
This research examines the improvement of learning achievement of Islamic Cultural History subjects with conventional learning methods and reading guides in students of class XI IIS MA Unggulan An Nuur Pare Kediri. Using the Classroom Action Research (PTK) approach, the results showed that the use of conventional learning methods and reading guides is effective and successful in improving student learning achievement. This is evidenced by the average learning value of students with the implementation of 3 (three) meetings experiencing an increase. Each action consists of planning, execution, observation, and reflection. The results showed that students' learning achievement increased starting from meeting I 60% then meeting II reached 80% next at the third meeting, to 86.7%, with an average final score of 80. To streamline the use of conventional learning methods and reading guides, the foresight of teachers is needed in realizing the level of understanding of students in receiving material. In this case, when it is felt that students feel saturated with the material and students do not understand the material well, the teacher must be able to provide a strengthening understanding of the material to increase the enthusiasm of students in learning.